Exercise for cancer cachexia in adults: Executive summary of a Cochrane Collaboration systematic review. Issue 3 (7th July 2015) - Grande, Antonio Jose; Silva, Valter; Maddocks, Matthew
Abstract: Background: Cancer cachexia is a complex syndrome characterized by an ongoing loss of skeletal muscle mass and progressive functional impairment. A proactive management approach is recommended, including physical exercise to maintain function via modulation of muscle metabolism, insulin sensitivity and levels of inflammation. The review aimed to determine the safety, acceptability and effectiveness of exercise in adults with cancer cachexia. Secondary aims, subject to the data availability, were to compare effectiveness according to the characteristics of the study intervention or population. Methods: We sought randomised controlled trials (RCTs) in adults meeting international criteria for cancer cachexia, comparing a programme of exercise as a sole or adjunct intervention to usual care or an active control. CENTRAL, MEDLINE, EMBASE, DARE and HTA, ISI Web of Science, LILACS, PEDro, SciVerse SCOPUS, Biosis Previews PreMEDLINE and Open Grey databases were searched up to June 2014. Two authors independently assessed studies for eligibility. Results: We screened 3154 separate titles and abstracts, and reviewed 16 full‐texts. Corresponding authors were contacted to determine if samples met cachexia staging criteria. Most authors did not explore this concept. No trial met review eligibility criteria. We were unable to perform a meta‐analysis to determine any effects from exercise intervention. Conclusion: Despite a strong rationale for the use of exercise, there is insufficient evidence to determine safety and effectiveness in patients with cancer cachexia. Findings from ongoing studies are awaited. Assessment of cachexia domains, ideally against international criteria, is required for future trials of exercise and supportive care interventions.